(untitled) - Prchal, Jan (Aura musica, 2014)
80th anniversary of Music Education Society - Importance of music education at present time - Standards of basic education, music in schools - workshops for teachers - 25th Summer workshop of music education 2014 Liberec - 2nd International Music Olympiad in Riga 2014.